ANALYSIS OF LANGUAGE FUNCTIONS IN GERMAN SONG “FÜR DIE LIEBE” FROM BERGE: SOCIOLINGUISTICS PERSPECTIVE - Fitri, Fitri; Akihary, Wilma; Sari, Dwi (Pattimura University, 2023)
Language is using by human as a medium to express the feelings, expressions, ideas, and thoughts, that not only realized through speaking or writing but also can realized through the literature works. One of the literature works is song. A song is a literary work that provides an opportunity for the author to express feelings, thoughts that are written down in verse of the song. Therefore, the researchers is interested in analyzing the function of language of German song lyrics in sociolinguistics. This research is a qualitative- descriptive research. The aim of this study is to describe the function of language in German song lyrics with the title für die Liebe from Berge. This study used read (listen) and note- taking technique as data collection techniques and descriptive analysis to analyze the data. The results showed that there are 7 language functions in that lyrics such as referential, poetic, instrumental, informative, imaginative, regulatory, and emotive language function. The significant finding: The findings of this analysis will help German language learners especially for provide information about the use of language in terms of its function. Keyword: language, function, analysis, German song, lyrics